You should look for two numbers whose product is 40, and whose sum is 13. Experimenting a little (trying different pairs of factors for 40), you can quickly realize that this works for 8 and 5. Therefore,
x2 + 13x + 40 = (x + 8) (x + 5)
Chat with our AI personalities
(x + 10)(x + 4)
-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)
You didn't bother to list the binomials to choose from, but the two binomial factors of x2 + 6x - 40 are (x + 10) and (x - 4)
(x + 10)(x + 4)
10(x+4)